Plastid-Localized EMB2726 Is Involved in Chloroplast Biogenesis and Early Embryo Development in Arabidopsis - Li, Chuanling; Shang, Jian-Xiu; Qiu, Chenlei; Zhang, Baowen; Wang, Jinxue; Wang, Shuo; Sun, Yu (Frontiers in Plant Science, 2021)
Embryogenesis is a critical developmental process that establishes the body organization of higher plants. During this process, the biogenesis of chloroplasts from proplastids is essential. A failure in chloroplast development during embryogenesis can cause morphologically abnormal embryos or embryonic lethality. In this study, we isolated a T-DNA insertion mutant of the Arabidopsis gene EMBRYO DEFECTIVE 2726 (EMB2726). Heterozygous emb2726 seedlings produced about 25% albino seeds with embryos that displayed defects at the 32-cell stage and that arrested development at the late globular stage. EMB2726 protein was localized in chloroplasts and was expressed at all stages of development, such as embryogenesis. Moreover, the two translation elongation factor Ts domains within the protein were critical for its function. Transmission electron microscopy revealed that the cells in emb2726 embryos contained undifferentiated proplastids and that the expression of plastid genome-encoded photosynthesis-related genes was dramatically reduced. Expression studies of DR5:GFP, pDRN:DRN-GFP, and pPIN1:PIN1-GFP reporter lines indicated normal auxin biosynthesis but altered polar auxin transport. The expression of pSHR:SHR-GFP and pSCR:SCR-GFP confirmed that procambium and ground tissue precursors were lacking in emb2726 embryos. The results suggest that EMB2726 plays a critical role during Arabidopsis embryogenesis by affecting chloroplast development, possibly by affecting the translation process in plastids.